2017
DOI: 10.1002/cem.2974
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning‐based genetic evolution of antitumor proteins containing unnatural amino acids by integrating chemometric modeling and cytotoxicity analysis

Abstract: Antitumor proteins (ATPs) are small oligoproteins or peptides that have been recognized as new and promising therapeutics against a variety of human tumors and cancers. In order to extend the structural diversity space of ATPs, the unnatural amino acids were incorporated into naturally occurring ATPs by using a chemometrics‐based genetic evolution strategy. Based on hundreds of ATPs derived from animals, plant and microbes statistical regression models were developed, optimized, and validated with a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The amino acids are usually polar, charged, and hydrophobic. Similarly, phenylalanine and leucine, as well as other hydrophobic amino acids accounted for more in the protein sequences [37]. The FTIR spectrum results indicated that there was a certain percentage of α-helix conformation in ASP-3.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acids are usually polar, charged, and hydrophobic. Similarly, phenylalanine and leucine, as well as other hydrophobic amino acids accounted for more in the protein sequences [37]. The FTIR spectrum results indicated that there was a certain percentage of α-helix conformation in ASP-3.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid descriptors were utilized as local descriptors to peptide sequence were derived from various physicochemical properties of 20 amino acids by using principal component analysis (PCA) . With amino acid descriptor characterization, the number of variables for a peptide is proportional to the peptide length, and thus, all the collected 12‐mer AIPs in the sample set would have the same number of variables generating from the characterization . The molecular structures of peptides were built and minimized with TINKER force field .…”
Section: Methodsmentioning
confidence: 99%
“…36 With amino acid descriptor characterization, the number of variables for a peptide is proportional to the peptide length, and thus, all the collected 12-mer AIPs in the sample set would have the same number of variables generating from the characterization. 37 The molecular structures of peptides were built and minimized with TINKER force field. 38 The structures were imported into CODESSA to generate more than 500 constitutional, topological, geometrical, charge-related, and thermodynamical descriptors.…”
Section: Structural Characterizationmentioning
confidence: 99%